2022
DOI: 10.3389/fpsyg.2021.800183
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19-Related Work Stress on the Mental Health of Primary Healthcare Workers: The Mediating Effects of Social Support and Resilience

Abstract: ObjectiveThe psychological condition of healthcare workers since the COVID-19 pandemic has attracted the attention of many studies. However, few have reported on psychosocial problems of primary healthcare workers in the COVID-19 pandemic. This study aimed to examine the mediating roles of social support and resilience in COVID-19-related work stress and symptoms of anxiety and depression.MethodsA total of 840 primary healthcare workers in 17 community health centers in Guangzhou, China, were recruited from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 70 publications
9
45
0
Order By: Relevance
“…Several original articles focusing on the COVID-19 pandemic, published after the search in October, 2020, support the findings in the present review: increased working hours and occupational stigma were associated with worse mental health and intention to leave among Taiwanese nurses [ 134 ]; mental health among primary healthcare workers in China was negatively affected by pandemic-related work stress; however, such stress was attenuated by social support and resilience [ 135 ]; and, finally, a Swedish longitudinal study found negative changes in healthcare staff’s working conditions and their possibility to recover after comparing their ratings before and after the first wave of COVID-19 [ 136 ].…”
Section: Discussionsupporting
confidence: 71%
“…Several original articles focusing on the COVID-19 pandemic, published after the search in October, 2020, support the findings in the present review: increased working hours and occupational stigma were associated with worse mental health and intention to leave among Taiwanese nurses [ 134 ]; mental health among primary healthcare workers in China was negatively affected by pandemic-related work stress; however, such stress was attenuated by social support and resilience [ 135 ]; and, finally, a Swedish longitudinal study found negative changes in healthcare staff’s working conditions and their possibility to recover after comparing their ratings before and after the first wave of COVID-19 [ 136 ].…”
Section: Discussionsupporting
confidence: 71%
“…In addition, this study showed that social support indirectly influenced depression and anxiety through mediation of resilience; therefore, hypothesis H4 was supported. Consistent with our results, previous studies have reported that resilience mediates the association between social support and mental health [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The mediation effect of resilience on the relationship between social support and subjective well-being has been reported among individuals with spinal cord injuries [ 30 ]. Moreover, a sequential mediating effect of social support and resilience on the association between COVID-19-related work stress and mental health outcomes, including depression and anxiety, has been reported [ 34 ]. Therefore, the association between COVID-19-related stress and mental health outcomes could be mediated by social support and resilience among young adults.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study conducted in China in July 2019, high scores of overcommitment and imbalance between effort and reward were associated with exhaustion, but not with professional efficiency, in HCW [ 27 ]. During the pandemic, overcommitment and a high imbalance in effort–reward were associated with insomnia [ 28 ], anxiety and depression [ 15 , 29 ], all of them reducing the effectiveness and efficiency of the medical services. Even more, one fifth of people affected by exhaustion will change their job in the following years [ 30 ], creating additional problems for the healthcare system in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between the fear of infection and transmission of the virus to others, exhaustion and burnout was assessed in different studies all around the globe [ 40 , 44 , 45 ]. It seems that, in some circumstances, pandemic fatigue was present also in medical institutions, with more unprotected exposure to COVID-19 in the third compared to the second wave [ 29 ]. The slHCW group was more critical about the risk management efficacy; there was a relation in the univariate analysis with the exhaustion score, but in the final adjusted model, this influence became non-significant.…”
Section: Discussionmentioning
confidence: 99%